DIAGNOSTIC OF THE POST GRADUATE UNIT OF UNMSM EDUCATION FACULTY - Barrientos Jiménez, Elsa Julia (2014)
This research consists of a diagnosis of the post graduate unit of UNMSM Faculty Education; it counts with the participation of 358 students of Second Specialty, Master and Doctorate programs. To carry out this diagnosis the instrument of the Iberoamerican University Association was taken into account. The following variables were used: students, teachers, study plans, research, management, surroundings, graduates and impact and evaluation. According to the established measurement the post graduate unit has obtained 69,27 points, which places it on a good level. This level considers a range point from 60 through 74.